2011
DOI: 10.5625/lar.2011.27.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofFicus caricapaste on constipation induced by a high-protein feed and movement restriction in beagles

Abstract: Constipation is one of the most common functional digestive complaints worldwide. We investigated the laxative effects of figs (Ficus carica L) in a beagle model of constipation induced by high protein diet and movement restriction. The experiments were consecutively conducted over 9 weeks divided into 3 periods of 3 weeks each. All 15 beagles were subjected to a non-treatment (control) period, a constipation induction period, and a fig paste treatment period. We administered fig paste (12 g/kg daily, by gavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…No abnormal symptoms were observed on serum and whole blood parameters [ 84 ]. Similar results were obtained in constipated beagles induced by a high-protein diet and movement restriction [ 85 ]. The ameliorating effect on constipation was believed to be attributed to cellulose, one of the main components of Ficus carica [ 84 , 85 ].…”
Section: Herbal Medicinesupporting
confidence: 86%
See 1 more Smart Citation
“…No abnormal symptoms were observed on serum and whole blood parameters [ 84 ]. Similar results were obtained in constipated beagles induced by a high-protein diet and movement restriction [ 85 ]. The ameliorating effect on constipation was believed to be attributed to cellulose, one of the main components of Ficus carica [ 84 , 85 ].…”
Section: Herbal Medicinesupporting
confidence: 86%
“…Similar results were obtained in constipated beagles induced by a high-protein diet and movement restriction [ 85 ]. The ameliorating effect on constipation was believed to be attributed to cellulose, one of the main components of Ficus carica [ 84 , 85 ]. Cellulose improved fecal excretion by increasing water content and bulk, elevating viscosity and shortening fecal transit time [ 86 ].…”
Section: Herbal Medicinesupporting
confidence: 86%
“…In a constipation rat model, supplementation with fig paste increased fecal output and water content, and decreased transit time (Lee et al, 2012a). Similar results with decreased transit time were found when fig paste was given to beagles with feed-induced constipation (Oh et al, 2011). In both studies, it was suggested that the motility effects were caused by the fiber content of the figs.…”
Section: Cysteine Proteases In Fruitssupporting
confidence: 58%
“…As with other diseases, for completion of treatment, constipation requires removing the primary causal factors. The first step, therefore, might be to change patient Ficus carica Moraceae Ficus carica and its fruit are used to treat chronic constipation [53].…”
Section: Discussionmentioning
confidence: 99%